Heat-wave tolerance in tropical intertidal animals: accounting for thermal and desiccation tolerances. (December 2019) - Miranda, Nelson A.F.; Peer, Nasreen; Ishak, Muhd Z.B.; Marshall, David J.
Highlights: Data on the response of non-model invertebrates to extreme climatic events. The response of sympatric thermophilic gastropod species to heat waves varies. Caution against generalizations on the impact of global warming on gastropods. Thermal and desiccation tolerances should be measured over longer periods of time. Abstract: We investigated whether thermal tolerance is useful in predicting the responses of tropical snails to heat-waves - unusually warm periods of weather. Studying four sympatric high-rocky-shore species, we assessed thermal tolerance from the lethal limit following a constant rate of acute warming, as well as from an ecologically-relevant heat tolerance measure accounting for midday thermal exposure times. These thermal tolerance assessments were then compared with the survival of snails under three laboratory-simulated heat-wave treatments, each constituting four days of cycling temperatures but varying in daily maximum temperature (45, 48 and 50 °C). Additionally, water loss of individual snails was measured daily to assess the effect of desiccation due to heat-wave exposure. We found that responses to heat-wave exposure are complex and are not always predictable from thermal tolerance traits. This arises from a mismatch in thermal tolerance and desiccation tolerance, such that variation in daily thermal maximum and duration of the heat-waves produced different survival responses for each species. This study highlights the need to consider both thermal and desiccation tolerance traits when building frameworks to predicting heat-wave vulnerability in benthic intertidal ectotherms.